Medijska pismenost kot pogoj uspešne politične socializacije - Erjavec, Karmen (Teorija in praksa, 2000)
Mass media are pervasive in contemporary society and their influence on leisure time, on the awareness of political and social reality. The danger to democratic values lies in the gap that has opened up between the relative sophistication and power of media procedurs and the relative passivity and lack of sophistication of media audiences. Media education is one way every culture possesses to addresses and hopefully to begin to close the gap. What kind of knowledge and skills are essential for being a citizen in a media age? Media education offers an answer - the ability to chose quality of information, analyse, criticaly evaluate and to produce media content, as wellas to foster the development of skills and practices integral to the practice of participatory democracy. Media literacy is an essential part of political socialization.
Keywords: communication sciences; komunikologija; vzgoja za medije; education; izobraževanje; politična socializacija; mass media; množični mediji